PERAN FOODHABITS MASYARAKAT PERDESAAN PESISIR DALAM MENDUKUNG KETAHANAN PANGAN: KASUS DESA BAHOI DAN BULUTUI DI KABUPATEN MINAHASA UTARA - Henny Warsilah (LIPI Press, 2013)
Coastal villages in eastern Indonesia have food diversity. Public consumption of staple food consisting of a mixture of rice and tubers, and bananas, which are cooked separately. Food habits indicates the diversity of food, has become a tradition and a part of the culture. This Food habits and food diversity in addition to support food security, also serves to keep the balance of nutrition. Food habits and food diversity owned coastal communities can be used as a model for the implementation of the diversification policy of food and nutrition balance for the community. Due to this movement launched by the government to diversify the food center has not shown tangible results, especially in Java, whereas in other parts of eastern Indonesia has a culture of food habits and food diversity practice is good. In that context variable ecosystems changes (ecological typology) and social typology is important to consider. While the conclusions obtained, the staple food habits mixture has reduced dependence on rice, and fish consumption and nutrient intake of protein is essential. Keywords: foodhabits, diversity of food, coastal community and food security.